A new stand-alone cage for cervical fusion Technique and early results - Yasser Allam (Egyptian Spine Association, 2014)
Background Data: After discectomy and anterior decompression, an intervertebral spacer is always necessary to promote fusion and to reconstruct cervical lordosis. The use of stand-alone cages is going to avoid the problems of graft donor site morbidity as well as the complications of the anterior instrumentation Purpose: The aim of this study is to present an intervertebral spacer that will provide the cervical spine with mechanical stability without the need for anterior instrumentation as well as a high fusion rate without the use of iliac bone graft. Study Design: Technical report Patients and Methods: The material of this study consisted of 50 patients with cervical radiculopathy. The mean age was 58.3 years. 55% of the patients were females. Patients were assessed pre-operatively and post-operatively using the Neck Disability Index (NDI) and the Visual Analogue Scale (VAS) for neck and arm pain. Fusion at the end of follow up was detected using X-Ray and multislice CT scans. Results: The mean operative time per level was 60 minutes. The average blood loss was 100 ml. There were no intraoperative complications. Preoperatively, the VAS neck was 6.8, VAS arm was 7.3 and NDI was 69. At the end of follow up the VAS neck improved to 3.7, VAS arm to 3.1 and NDI to 26. Fusion occurred in 98% and cage subsidence was observed in 8% of patients. Conclusion: In comparison to other intervertebral cervical spacers, we think that we are going to achieve good clinical results with improved fusion rate. (2014ESJ060)